Aplikasi Transportasi Online GO-JEK Bentuk dari Konstruksi Sosial Teknologi dalam Media Baru - Henry Brown Nathalia; Irwansyah Irwansyah (MediaTor (Jurnal Komunikasi), 2018)
Technology is something that can’t be separated from the life of modern societies today. Technology is present to help man to run their daily activities. Are humans as creators of technology, or technology that shapes humans in such a way? This question tried to answer by the Social Construction of Technology theory, this theory views that man determine technology. Social Construction of Technology is condition in which the society needed and make technology because of their social necessity. It means, human and technology can not be separated. People will continue to need technology and innovate to create new technologies to make their daily activities easier. the presence of online transportation apps, as a concrete example of the  implementation of social construction technologies in new media, online  transpotation applications such as GO-JEK were created as a solution for the society to resolve traffic jam problems and their needs for easier transportation that fast and efficient.